Short-term and mid-term survival of VA-ECMO patients: a single-center experience - Barshatskyi, Artur; Vicha, Marek; Klementova, Olga; Zapletalova, Jana; Zuscik, Ondrej; Santavy, Petr; Juchelka, Jan; Konecny, Jakub; Simek, Martin (Kardiochirurgia i torakochirurgia polska, 2025)
INTRODUCTION: Extracorporeal membrane oxygenation (ECMO) is a rescue method in the treatment of severe cardiac or respiratory failure in patients with various etiological factors contributing to this failure and of different ages. The question of ECMO support for patients has recently arisen more frequently, due to the expansion of indications for this method and an increase in the number of patients with severe cardiac or respiratory failures. AIM: To present a single center's 10-year experience with ECMO support, outcomes and mortality. MATERIAL AND METHODS: A retrospective single-center study was conducted on patients with VA-ECMO for cardiac and/or respiratory indications. In this retrospective study, the treatment outcomes of patients undergoing VA-ECMO over a 10-year period within one ECMO center were analyzed, focusing on hospitalization mortality (mid-term outcomes). Additionally, the structure of treated patients was analyzed secondarily according to age, gender, and length of hospitalization. RESULTS: Out of 114 patients treated with VA-ECMO, 34.2% survived for 30 days, 28.1% survived for 90 days, and 26.3% survived for 12 months. The median age of the patients was 58 years. The median duration of cardiopulmonary support was 2.6 days and duration of hospitalization after support explantation was 2.5 days. There was no significant difference between men and women in terms of age, length of hospitalization, hospitalization mortality, and survival at 30 days, 90 days, and 12 months. CONCLUSIONS: The use of VA-ECMO support in patients with severe to critical cardiopulmonary failure is a commonly employed method in many centers. Data analysis reveals high hospitalization mortality. No predictive factors for short-term and medium-term survival were identified among patient age, gender, duration of support, and length of hospitalization after VA-ECMO support explantation.
Keywords: short-term; mid-term survival; extracorporeal membrane oxygenation; hospitalization mortality